Chemistry of Atmospheric Fine Particles During the COVID‐19 Pandemic in a Megacity of Eastern China. Issue 2 (18th January 2021) - Liu, Lei; Zhang, Jian; Du, Rongguang; Teng, Xiaomi; Hu, Rui; Yuan, Qi; Tang, Shanshan; Ren, Chuanhua; Huang, Xin; Xu, Liang; Zhang, Yinxiao; Zhang, Xiaoye; et al.
Abstract: Air pollution in megacities represents one of the greatest environmental challenges. Our observed results show that the dramatic NOx decrease (77%) led to significant O3 increases (a factor of 2) during the COVID‐19 lockdown in megacity Hangzhou, China. Model simulations further demonstrate large increases of daytime OH and HO2 radicals and nighttime NO3 radical, which can promote the gas‐phase reaction and nocturnal multiphase chemistry. Therefore, enhanced NO3 − and SO4 2− formation was observed during the COVID‐19 lockdown because of the enhanced oxidizing capacity. The PM2.5 decrease was only partially offset by enhanced aerosol formation with its reduction reaching 50%. In particular, NO3 − decreased largely by 68%. PM2.5 chemical analysis reveals that vehicular emissions mainly contributed to PM2.5 under normal conditions in Hangzhou. Whereas, stationary sources dominated the residual PM2.5 during the COVID‐19 lockdown. This study provides evidence that large reductions in vehicular emissions can effectively mitigate air pollution in megacities. Plain Language Summary: Megacities in developing countries such as China and India are facing severe air pollutions. There are still large uncertainties in quantifying the sources of fine particles at the citywide scale due to the synergetic effects of complex aerosol chemistry and transboundary transport. The COVID‐19 lockdown led to the lowest intensity of human activities in recent decades, which provides a unique opportunity to gain insights into the relationship between emission sources and aerosol chemistry. The COVID‐19 lockdown led to significant decreases of PM10, PM2.5, CO, SO2, and NOx, whereas O3 increased by more than a factor of 2 in megacity Hangzhou, China. The filter‐based PM2.5 chemical analysis and model simulation show that although enhanced oxidizing capacity promoted the secondary aerosol formation during the COVID‐19 lockdown, the PM2.5 concentrations still largely decreased by 50%, in which NO3 − had the largest decrease of 68% whereas SO4 2− only decreased by 5%. This result indicates that the reduction in vehicular emissions contributed significantly to the PM2.5 decrease during the COVID‐19 lockdown. We highlight that to mitigate air pollution in megacities, regulations on vehicular emissions, deeper energy and industrial restructuring, and regional joint‐controls should be taken in the future. Key Points: Air pollutants PM10, PM2.5, NOx, CO, and SO2 decreased whereas O3 increased during the COVID‐19 lockdown in megacity Hangzhou Enhanced NO3 − and SO4 2− formation caused by the enhanced oxidizing capacity partially offset the decrease of PM2.5 in megacity Hangzhou The contribution of vehicular emissions to PM2.5 was over stationary sources under normal conditions in megacity Hangzhou